Možnosti uporabe robotike spodnjih udov v rehabilitaciji oseb z okvaro hrbtenjače - Birk, Klara (Rehabilitacija (Ljubljana), 2022)
Incorporating robotics enables preparation and beginning of gait training early in the rehabilitation process, which also influences the psychological state and quality of life of a person with spinal cord injury through the effect on various body systems. In the early mobilisation phase, tilt table in combination with functional electrical stimulation and stepping provides beneficial effect on longer maintenance of upright position. During the rehabilitation process in patients with incomplete upper motor neuron lesion, static exoskeletons allow the selection and adaptability of bodyweight support according to the gait cycle during treadmill training. End-effector devices enable gait and stair-climbing training through control of the distal part of kinetic chain with varying guidance force and body-weight support. Exoskeletons and devices for body-weight support, which are patient guided, can also be used as an aid for over-ground walking, getting up and sitting down exercises, and climbing stairs. Whether robot-assisted therapy is more efficient than conventional therapy remains unknown.
Keywords: early mobilisation; gait; hoja; neurological rehabilitation; nevrološka rehabilitacija; rehabilitation; robotic exoskeleton; Robotics; robotizirani eksoskelet; Spinal Cord; zgodnja mobilizacija